Mecanismos de proteção mediados pela resposta imune na ascaridiose larval após exposição primária e múltiplas exposições ao parasito - Denise Silva Nogueira (2018)
Human ascariasis is the most prevalent neglected tropical disease in the world affecting about 800 million people. In endemic areas, reinfection is recurrent due to poor basic sanitation conditions and, above all, the readiness of the parasite life cycle. After ingestion of infective eggs, third stage larvae (L3) hatches and penetrates the large intestine, gaining blood circulation and reaching the liver and later the host lungs, characterizing larval ascariasis. In these organs, L3 migrates generating both mechanical lesions and intense inflammatory response, which is characterized mainly by intense neutrophil and eosinophil infiltration. The present work aimed to describe and characterize the pathophysiological effects of the Ascaris suum larvae migration on the lungs of infected mice, as well as to evaluate the role of eosinophils and regulation of the Th1, Th2 and Th17 responses in the pathogenesis of larval ascariasis after single- and re-infection. For this, parasitological and immunopathological evaluation was initially performed in BALB / c mice single- and re-infected during the peak of larval migration within the liver, lung and intestine. Afterwards, mice genetically deficient in GATA1, IFN-γ, IL-17RA, ST2, IL-4 and the respective wild-type were infected and re-infected and, after eight days of infection, underwent immunoparasitological and pathophysiological evaluation. The most important results of this work demonstrated that re-infected mice presented a significant reduction of the parasitic load in the lung and increased cellularity in the bronchoalveolar lavage (BAL) associated to an intense granulocytic pulmonary inflammation, which led to a compromised respiratory function. It was evidenced that mixed pulmonary inflammation is of extreme importance for the control of larval migration. However, regarding Th2 / Th17 responses, they are associated with a greater impairment of pulmonary function, especially Th2. In addition, this work has brought strong evidence of the contribution of eosinophils in a ascariasis multiple exposition model. It was evidenced that eosinophils are indispensable for the production of SIgA in the pulmonary mucosa and that these cells depend on the signaling by TLR2 and TLR4 activation to induce SIgA production in the mucosa and to control the parasitic load. It has been demonstrated that eosinophils contribute to pulmonary parenchymal fibrosis in response to A. suum tissue damage. Extrapolating to the current scenario of human ascariasis, the data of this work could also explain the epidemiological distribution of Ascaris sp. since most of the infected individuals in high endemicity areas, where they are exposed multiple times to the parasite, present low parasitic load.